2019
DOI: 10.1021/acsnano.9b01892
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Mesenchymal Stem Cell Derived Exosomes Loaded with Phosphatase and Tensin Homolog siRNA Repairs Complete Spinal Cord Injury

Abstract: Individuals with spinal cord injury (SCI) usually suffer from permanent neurological deficits, while spontaneous recovery and therapeutic efficacy are limited. Here, we demonstrate that when given intranasally, exosomes derived from mesenchymal stem cells (MSC-Exo) could pass the blood brain barrier and migrate to the injured spinal cord area. Furthermore, MSC-Exo loaded with phosphatase and tensin homolog small interfering RNA (ExoPTEN) could attenuate the expression of PTEN in the injured spinal cord region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
245
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 320 publications
(263 citation statements)
references
References 97 publications
0
245
0
Order By: Relevance
“…A multimodal approach provides the potential to make use of the advantages of each modality while reducing the overall drawbacks. Exosomes measureable by both CT and FLI can be tracked in vivo using CT, and then more precisely ex vivo with FLI (Guo et al, 2019). Also, this approach allows for self-validation, since a measured result can be confirmed by the other modalities (C. P. Lai, Mardini, Ericsson, et al, 2014;Yuki Takahashi & Takakura, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A multimodal approach provides the potential to make use of the advantages of each modality while reducing the overall drawbacks. Exosomes measureable by both CT and FLI can be tracked in vivo using CT, and then more precisely ex vivo with FLI (Guo et al, 2019). Also, this approach allows for self-validation, since a measured result can be confirmed by the other modalities (C. P. Lai, Mardini, Ericsson, et al, 2014;Yuki Takahashi & Takakura, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al tested in experimental SCI models loaded with PTEN-siRNA-MSC-exo. The exosome could able to carry PTEN-siRNA to the target tissues e ciently and augment the regenerative effect by promoting more robust axon regeneration after SCI [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes were suspended in 70ml PBS and were centrifuged for 90 minutes at 100,000g at 4˚C. The pellet was suspended in 200 µL of PBS [14][15][16] .…”
Section: Exosomes Labelingmentioning
confidence: 99%
“…We have previously shown that MSC-exo migrate to damaged tissues in the brain after intranasal administration [14][15][16] . In the BTBR mice model of autism we saw MSC-exo accumulating in the areas of the frontal cortex and the cerebellum while in WT C57BL/6Jmice we could not detect any accumulation and the MSC-exo evacuated out of the brain within 24h.…”
Section: Msc-exo Cross the Blood Brain Barrier After Intranasal Adminmentioning
confidence: 99%
See 1 more Smart Citation